Growth and Yield Response of Rice (Oryza sativa L.) to Compound Copper and Zinc Micronutrient Fertilization - Sutan Tarmizi Lubis; Eka Tarwaca Susila Putra; Betha Silmia (Jurnal Biologi Tropis, 2026)
This study evaluated a Zn–Cu compound micronutrient fertilizer on plant growth, yield components, grain yield, and fertilizer-use efficiency of Inpari 32 rice. A field experiment was conducted in an Inceptisol paddy field (1,100 m²) in Margokaton, Seyegan, Sleman, Yogyakarta, Indonesia (January–April 2025). Treatments were arranged in a non-factorial completely randomized design with eight fertilizer regimes and four replications, combining NPK with graded rates of Zn+Cu fertilizer. Pre- and post-planting soil nutrient analyses and post-harvest leaf tissue nutrient analyses were conducted, and vegetative traits, yield, Relative Agronomic Effectiveness (RAE), and fertilizer-use efficiency were evaluated. Soil Zn and Cu were initially very high and high, respectively, but remained below toxicity thresholds. Compared with regimes without Zn+Cu, Zn+Cu additions significantly increased plant height, tiller number, and milled dry grain yield. Treatments P2–P7 achieved RAE >100%, indicating greater agronomic effectiveness than the non-Zn+Cu regimes. The most effective dosage was P6 (1 dosage NPK + 1.5 dosage Zn+Cu).